(3QSGdI GdMOhO aj CSHGH MOhK GdMQhas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jSJMbg dYXeI PGJg hSYI QMeJg haVd LhOg hGdJeS efi HGSW dGeMJGL Cf CcJH HESeg eG MUd YfOi HYO GdHMK hGdeSJbUi ef GSHGH ai GdeSehY ai QSGdI hLjRg LOkG s
(3BNQgG (B:s
(3hYHQJ Yf GdebOGQ GdPi eHdZg efi GdeYQaI JbQHkG Edi GdTjN GdcQje GdGSJGP gGgfG CNJe GdQSGdI eJhcdkG Ydi Gddg hgh MSHi hfYe Gdhcjd hGdMeO ddg Mb MeOg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B861s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs